IJCM_137A: A cross-sectional study to find out prevalence of alcohol, smoking and other substance abuse among adolescent in Raipur city, Chhattisgarh - Jaiswal Prashant Kumar; Verma Nirmal (Wolters Kluwer Medknow Publications, 2024)
Background: The use of various psychoactive substances such as alcohol, cannabis and opioids has been observed in India for centuries, the current dimension of the extent and pattern of psychoactive substance use and the problems associated with their use are not well-documented. Substance use estimates from 2004 indicate that tobacco, alcohol and illicit drugs account for 8.7%, 3.8% and 0.4% of all deaths respectively, and 3.7%, 4.5% and 0.9% of Disability Adjusted Life Years (DALYs) lost respectively. National-level prevalence has been calculated for many substances of abuse, but regional variations are quite evident. Rapid assessment surveys have facilitated the understanding of changing patterns of use. Substance use among women and children are increasing cause of concern. Objective: To find out the prevalence of substance use among adolescentsat Raipur City C.G. Methodology: Study design: Community-based cross-sectional observational study. Study centre: Department of Community Medicine, Pt. JNM Medical College, Raipur Study area: Raipur city Study technique: Interview method Sample size: 300 Results: In the present study among 664 adolescents, 301 (45.3%) have a lifetime history of any type of substance abuse other than their medicinal use. The majority 53.5% and 26.8% belong to class II & III socioeconomic status as per the revised modified Prasad classification 2023. 39.5%, 17.6% and 5.7% of adolescents have a lifetime exposure to any form of Tobacco, alcohol & cannabis abuse respectively. Conclusion: In the present study, the prevalence of substance abuse is very high among adolescents and we found that 39.5% of adolescents are exposed to tobacco products while the Global Youth Tobacco Survey-4 (2019) estimates it was 18.1%.